An IoT-based Instrument for free fall motion / Kevin Josel … [et al.] - Josel, Kevin; Lestari, Aura Angel; Ramadhan, Nur Faiq; Nazirah, Amatun; Sesa, Elisa (Faculty of Computer and Mathematical Sciences, 2023)
This project presents the development and implementation of an innovative Internet of Things (IoT) instrument designed to investigate the dynamics of objects in free-fall motion. Leveraging the power of Arduino-based hardware and IoT connectivity, the instrument offers a versatile platform for measuring the gravitational acceleration of objects in free fall. The IoT integration empowers observers to remotely operate the instrument. The instrument consists of three key components: a mechanical system, an electrical system, and an IoT system, each playing a pivotal role in its functionality. The mechanical system is composed of a stepper motor with a pulley connected to a rope, a moving pad with a solenoid, an iron pole, and a limit switch, working in tandem to facilitate the instrument's mechanical functions. The instrument has operated and works well.